Comparison of the immunoassay method with the commercial and in-house LC-MS/MS methods for substance abuse in urine - Avcioglu Gamze; Yilmaz Gulsen; Yalcin Sahiner Safak; Kozaci L. Didem; Bal Ceylan; Yilmaz Fatma Meric (Türk Biyokimya Dergisi, 2023)
The aim of this study was to compare the analytical performance of the KIMS (kinetic interaction of microparticles in solution) immunochemical method with a validated in-house and a commercial LC-MS/MS method.